Successful treatment of a spontaneous right coronary artery dissection with a 4-mm diameter cutting balloon: a case report. Issue 4 (27th November 2019) - Sharma, Harish; Vetrugno, Vincenzo; Khan, Sohail Q
Abstract: Background: Guidelines recommend conservative management for a spontaneous coronary artery dissection (SCAD) in the absence of ongoing ischaemia, haemodynamic instability, or left main dissection. Conventional percutaneous coronary intervention methods for SCAD are associated with an unfavourable prognosis due to difficulties wiring the lesion, dissection propagation, and potential 'milking' of the intramural haematoma along the vessel or into other vessels. These factors promote implantation of multiple stents which are often undersized, increasing the risk of in-stent restenosis significantly. There have been several case reports demonstrating the novel use of small diameter cutting balloons in the left anterior descending artery system. Here, we describe the successful use of a larger 4 mm cutting balloon to treat a spontaneous right coronary artery (RCA) dissection. Case summary: A 53-year-old woman with troponin negative chest pain and was diagnosed with unstable angina due to ischaemic electrocardiographic features. Coronary angiography revealed a tight discrete lesion in the RCA. Intravascular imaging confirmed SCAD and a 4 mm cutting balloon was used to dissect the tunica intima to allow complete resorption of the intramural haematoma and resolution of symptoms. Discussion: This case demonstrates the safe use of a larger 4 mm cutting balloon to treat an RCA SCAD, resulting in complete resolution of the haematoma.